Wool Sector Analysis for Pakistan - Shabbir, Muhammad (Advances in Social Sciences Research Journal, 2016)
There is a great prospective to develop wool sector as industry and economically viable rural avocation in Pakistan. It is a labor intensive and combines both Industry and livestock. It generates quick returns on low investment, is a source of self employment, and generates exports and foreign exchange earnings. Objective and scope of this basic and exploratory research is to the map and value chain of wool sector right from the livestock breeding and handling to value added wool products in Pakistan. This research study will based on both quantitative and qualitative data set as it involves surveying of wool related establishments all over Pakistan, as well as qualitative data and validation of analysis by the stakeholders. This Mapping study will include Objectives, SWOT Analysis, and Market Analysis; SWOT Analysis for wool sector in Pakistan This study will present recommendations for the growth of the sector. It will also be useful in providing an understanding of complete process to the policy makers for poverty reduction and tackling unemployment. And it will serve as database for short term and long term planning and future research.